SIMULASI INTEGRASI PV-BIOGAS MENGGUNAKAN HOMER PADA PEMBANGKIT LISTRIK HYBRID ON - GRID: STUDI KASUS PONPES BAITURRAHMAN CIPARAY BANDUNG - Ahmad Rajani; Kusnadi Kusnadi; Rudi Darussalam (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This paper discussed the simulation integration from several renewable energy sources, software HOMER were used to simulate hybrid (PV-Biogas) on grid electicity generation. The parameters observed in this simulation are the cost of energy (COE), where the optimal plant is the one that has the lowest COE. This reserch was conducted at Ponpes Baiturrahman Ciparay, Bandung which is the location of the field laboratory of hybrid power generation from renewable energy sources. Homer will be simulatied using combination of hybrid power plant on the optimum grid to supply electricity at the designated location. The simulation result using this software shows that a combination of on grid hybrid power plants can increase COE at $ 0,113 / kWh (PLN) to $ 0,186 / kWh (hybrid on grid). This indicates that the electrical energy generation from renewable energy sources is still expensive, so government must create regulation to provide subsides for rewnable energy sourced electricity.Keywords : Electricity, hybrid On Grid, Cost Of Energy, Homer.